REPRESENTING BANDUNG AS THE EMERGING FASHION CAPITAL OF INDONESIA: BANDUNG FASHION HUB DI CIKAPAYANG, TAMANSARI, KOTA BANDUNG - Anatri Yasmin, Namira
In actualizing Bandung as a fashion capital of Indonesia, it is very important to maintain the sustainability of the fashion industry in it and make this industry as a major force for the city's economy. Through a place that can accommodate the development of the fashion industry in the city of Bandung, interactions will be triggered between the people working in the fashion industry, so then creations and innovations can continue to be carried out in this industry. Hence, the Ministry of Tourism and Creative Economy of the Republic of Indonesia initiated the Bandung Fashion Hub project. This project is proposed to be built in Cikapayang, Tamansari, Bandung City, the location is considered very strategic because it is in the center of the city of Bandung with the surrounding context being dominated by a commercial zone, and this building will also have a high visibility because of the existing landform. This 8204.6 m2 building has five floors and three masses that cover the main functions of exhibition, education, and commercial. Not only professionals and students in the fashion industry, but also the general public can all use this building. The activities carried out by the users of this building will vary, ranging from the main activities such as exhibitions and fashion shows, to supporting activities such as workshops and buying and selling. Design issues that are prioritized in the design of the Bandung Fashion Hub include zoning, the image of the building, ambience, and social interaction. Based on the characteristics of fashionistas, the urban context, and the project objective being a representation of the fashion industry in Bandung, several basic design concepts were born, namely "Free Fashion Show" and Fashionable Architecture. Based on the behavioral analysis of fashionistas, where usually they have a high desire to be seen, and also adjusting to the context of the site, the rooms in the building are made more visible and easily accessible from all outside the building. Wrapped in a commercial atmosphere, visitors are made as if they are doing a “free fashion show” while visiting this building. Based on the image of the building which is expected to be a representation of fashion, the composition of the masses and the facade are made different from the surrounding context, where the shape of the building is made curvy, contrary to the shape of the surrounding buildings to produce an iconic and fashionable impression.